Glucosinolate Diversity Analysis in Choy Sum (Brassica rapa subsp. chinensis var. parachinensis) Germplasms for Functional Food Breeding - Seong-Hoon Kim; Parthiban Subramanian; Bum-Soo Hahn (Foods, 2023)
The aim of this study was to analyze glucosinolates (GSLs) in germplasm that are currently conserved at the RDA-Genebank. The analysis focused on the glucosinolate diversity among the analyzed germplasms, with the goal of identifying those that would be most useful for future breeding efforts to produce nutritionally rich Choy sum plants. In total, 23 accessions of Choy sums that possessed ample background passport information were selected. On analyzing the glucosinolate content for 17 different glucosinolates, we observed aliphatic GSLs to be the most common (89.45%) and aromatic GSLs to be the least common (6.94%) of the total glucosinolates detected. Among the highly represented aliphatic GSLs, gluconapin and glucobrassicanapin were found to contribute the most (>20%), and sinalbin, glucoraphanin, glucoraphasatin, and glucoiberin were detected the least (less than 0.05%). We identified one of the accessions, IT228140, to synthesize high quantities of glucobrassicanapin and progoitrin, which have been reported to contain several therapeutic applications. These conserved germplasms are potential bioresources for breeders, and the availability of information, including therapeutically important glucosinolate content, can help produce plant varieties that can naturally impact public health.